STRATEGI PENINGKATAN PENANGGULANGAN BENCANA KEBAKARAN DI KABUPATEN SUMBAWA BARAT - MARANTIKA, HENDIRIA; ZAINUDDIN, ZAINUDDIN; NURJADDIN, RUSMIN (GANEC SWARA, 2023)
This research discusses strategies to improve fire disaster management in West Sumbawa Regency. The background of this research is because the Minimum Service Standards for fire management in all areas of West Sumbawa Regency have not been achieved due to geographical, area, and demographic factors compared to the number of Fire Fighting Unit Members and inadequate fire management infrastructure. The purpose of this study was to determine strategies to improve fire disaster management in West Sumbawa Regency in achieving Minimum Service Standards. This research uses a quantitative method using SWOT analysis based on the results of a questionnaire to 10 respondents determined by purposive sampling to determine strategies for improving fire disaster management at the Fire and Rescue Service of West Sumbawa Regency. The results of the SWOT analysis can be formulated a strategy for improving fire management in West Sumbawa Regency is to support aggressive strategies by increasing the synergy of Regional Apparatus Organizations, increasing the competence of Fire Fighting Unit Members with education and training, forming Fire Fighting Volunteers and increasing the budget for improving fire facilities and infrastructure.